KRIMINALITAS DI KALANGAN REMAJA (STUDI TERHADAP REMAJA PELAKU PENCABULAN DI LEMBAGA PEMASYARAKATAN ANAK KELAS II B PEKANBARU) - Putra, Redian Syah; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Abuse is act that violates decency or indecency relating to sex appetite, which directly or indirectly is agains decency and can be convicted. Acts of abuse is one that criminal cases that experienced a huge increase in recent years. As so as the number of abuse in Pekanbaru. Penitentiary class II B for children in Pekanbaru, number of abuse act by teenagers is a very high number compared to other criminal acts which is 24 people on July and August 2015. This study aims to find out the factors causing teenagers doing act of abuse and to know the types of action forms by the teenagers. This study uses the theory of Sosial Deviation which is using books about deviant behavior and socialization. The data collection techniques used interview techniques and documentation. The data analysis method used is descriptive qualitative analysis. The determination of the sample by random sampling technique, namely the selection of a random sample. The results of the study explained that no single factor that causes teens perform obscene acts, but an association from each factors that led to commit sexual abuse. With generally forms based on consensual abuse and there is also the element of violence. Acts of abuse arises from a lack of understanding of the values and norms as well as the process which is not perfectly socialized. Society need to understand the values and norms that exist in society to avoid deviant behavior.Keyword: Abuse, Teenagers , Sosial Deviation